2020
DOI: 10.5430/jnep.v10n5p100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of EMBODY Experiencing Dementia through New Media Exhibit: Engaging nursing students and the public about dementia through arts-based knowledge translation methods

Abstract: Objective: This paper aims to look at the impact of arts-based knowledge translation (ABKT) methods in raising awareness among nursing students and the public about the sex differences and behavioral and psychological symptoms of dementia (BPSD), implemented through a creative new media arts-exhibit at Toronto Rehabilitation Institute.Methods: Through surveys, interviews, and pre- and post-exhibit questionnaires, this project evaluated the use and efficacy of multi-modal media in translating data from a study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A multimedia arts exhibit in Canada, about the experience of living with dementia, including VR, was evaluated using mixed methods. Researchers concluded that it increased empathy and understanding of dementia among nursing students, with VR being among the most engaging media [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multimedia arts exhibit in Canada, about the experience of living with dementia, including VR, was evaluated using mixed methods. Researchers concluded that it increased empathy and understanding of dementia among nursing students, with VR being among the most engaging media [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18] The videos used for the study were from the point of view of a person with dementia, with the use of editing technology to create agitation and perceptual distortions that are typically experienced with dementia. [6] By viewing these videos with the 360-degree video technology, an immersive experience of what it feels to have dementia was created.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[21] By utilizing 360degree immersive videos from male and female perspectives, the study aimed at cultivating a deeper awareness of the BPSD, alongside prominent sex differences, in users, as they experienced, first-handedly, the challenges that persons with dementia face. [6] This ultimately helps to reduce caregiver stress and burden, and contributes to better care provision for the person with dementia. [22,23] 3.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have tested whether viewing artist-produced photographs can improve the mood, well-being, and social interactions of people with dementia [34][35][36][37][38]. However, few projects have used photography as a tool for nursing education about dementia [39], and none that we could find have previously employed a photobook in an educational intervention.…”
Section: Introductionmentioning
confidence: 99%